Mastitis Detection in Holstein Sahiwal Crossbred Cattle (Bos taurus) Using Different Brands and Dilution Levels of Liquid Anionic Surfactants - Waminal, Yancy Ogdamin; Gambol, Marjorie Raboy; Sabado, Ahron Caiman; Vallejos, John Paul Muring; Briones, Ronaldo Curameng; Estabillo, Esteward Jones Manlangit (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2021)
The study was conducted to evaluate the effect, consistency, and economic viability of using different brands and dilution levels of liquid anionic surfactants to detect Mastitis in dairy cattle. Fifty-five milk samples were collected and subjected to macroscopic evaluation at a cattle farm located in Sta. Maria, Bulacan, Philippines. Milk samples were brought to the Philippine Carabao Center National Headquarters and Genepool Science City of MuÃ±oz, Nueva Ecija for Somatic Cell Count. The experiment used 10 treatments with 3 replications arranged in a Completely Randomized Design. The macroscopic evaluation results showed that liquid anionic surfactants at 30%-50% dilution levels could detect Mastitis in dairy cattle. This was validated by the somatic cell count results from PCC Dairy Laboratory. On the other hand, statistical analysis results revealed that the treatments and the control (commercial mastitis test) were comparable except for brand Z at a 40% dilution rate. Brand Z at 30% and 50% dilution rate were found to be consistent among other treatments in detecting Mastitis in dairy cattle. In terms of economic viability, brand X and brand Y at 30% were the cheapest and had the lowest production cost and highest percentage savings. The study was conducted to evaluate the effect, consistency, and economic viability of using different brands and dilution levels of liquid anionic surfactants to detect Mastitis in dairy cattle. Fifty-five milk samples were collected and subjected to macroscopic evaluation at a cattle farm located in Sta. Maria, Bulacan, Philippines. Milk samples were brought to the Philippine Carabao Center National Headquarters and Genepool Science City of MuÃ±oz, Nueva Ecija for Somatic Cell Count. The experiment used 10 treatments with 3 replications arranged in a Completely Randomized Design. The macroscopic evaluation results showed that liquid anionic surfactants at 30%-50% dilution levels could detect Mastitis in dairy cattle. This was validated by the somatic cell count results from PCC Dairy Laboratory. On the other hand, statistical analysis results revealed that the treatments and the control (commercial mastitis test) were comparable except for brand Z at a 40% dilution rate. Brand Z at 30% and 50% dilution rate were found to be consistent among other treatments in detecting Mastitis in dairy cattle. In terms of economic viability, brand X and brand Y at 30% were the cheapest and had the lowest production cost and highest percentage savings.